Pembuatan Website Bertemakan OpenSID di Desa Petak Kabupaten Gianyar - I Putu Elmo Bertrand Mahamega; A. A. Istri Ita Paramitha; I Gede Juliana Eka Putra (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Desa Petak, located in Gianyar District, Gianyar Regency, Bali Province, still faces limitations in managing digital-based administrative services, including the absence of an official village website. Village information systems hold an important role in supporting transparent and efficient village governance. This study aims to apply an OpenSID-based village information system as an effort to improve the quality of administrative services in Desa Petak. The research method consisted of needs analysis, data collection, development of the OpenSID website, system management assistance, and evaluation through questionnaires distributed to village officials. The results indicate that the application of OpenSID supports more structured population data management and administrative services. Post-training evaluation shows an improvement in village officials' understanding of the OpenSID system as well as increased ease in administrative service processes. The application of OpenSID provides a positive contribution to accelerating digital village development and improving the quality of public services at the village level.